3a^5 - (-a^5) = 3a^5 + a^5 = 4a^5
6a^7 - 2a^7 = 4a^7
-3a^5 - (-2a^5) = -3a^5 + 2a^5 = -a^5
7a^7 - 8a^7 = -a^7
Any arithmetic sequence can be expressed as:
a(n)=a+d(n-1), a=initial term, d=common difference, n=term number
In this case a=5, and d=-2 so
a(n)=5-2(n-1) which can be simplified...
a(n)=5-2n+2
a(n)=7-2n
The domain is restricted to integers from 1 to +oo.
Answer:
360 votes
Step-by-step explanation:
Move the decimal to the left 2 times and you'll get .144. Multiply that by 2500, and you have your answer.
Step-by-step explanation:
3 : x = -7.5
5 : x = -10
6 : x = 12
remaining answers are correct
Answer:
Step-by-step explanation:
Ur mom